Lower Extremity Salvage in the Setting of Bullous Pemphigoid Exacerbation: A Case Report. Issue 8 (August 2021) - Pollock, Samara E.; Rice, Shauna M.; Ferree, Sarah D.; Friedstat, Jonathan; Eberlin, Kyle; Kourosh, Arianne S
Abstract : Summary: Bullous pemphigoid is an autoimmune blistering disease where patients suffer from painful bullae, often covering large portions of the skin and requiring management with immune-suppression. Our case report of recurring bullous pemphigoid illustrates the importance of considering immunosuppressive perioperative management in patients with a history of autoimmune blistering even when the disease has been quiescent for some time. With multidisciplinary care and immune suppressive therapies in the perioperative period, a free flap complicated by recurrent bullous pemphigoid can be salvaged.